THE PEDAGOGICAL POTENTIAL OF CULTURAL-EDUCATIONAL PRESCHOOL ENVIRONMENT IN THE INTER-ETHNIC TOLERANCE UPBRINGING PROCESS - Katerina Romaniuk (Vasyl Stefanyk Precarpathian National University, 2015)
In the article the author focuses attention on the need of early education of inter-ethnic tolerance and anticipates increasing of the efficiency of the process by the pedagogical potential of cultural-educational environment of preschool. Author investigates the Ukrainian and foreign scientific approaches of the interpretation the concept "cultural-educational environment" and identifies its major components. The paper accented that preschool educational space helps to upbring foremost ethic-cultural competence of preschoolers and then nurture respect and friendliness to other nationalities. Author outlines a significant role of the organization and specific filling with different objects in the preschool playing area, proposes the ways to model it.